2015
DOI: 10.1038/srep15865
|View full text |Cite
|
Sign up to set email alerts
|

Recent Arctic tundra fire initiates widespread thermokarst development

Abstract: Fire-induced permafrost degradation is well documented in boreal forests, but the role of fires in initiating thermokarst development in Arctic tundra is less well understood. Here we show that Arctic tundra fires may induce widespread thaw subsidence of permafrost terrain in the first seven years following the disturbance. Quantitative analysis of airborne LiDAR data acquired two and seven years post-fire, detected permafrost thaw subsidence across 34% of the burned tundra area studied, compared to less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 52 publications
5
137
0
Order By: Relevance
“…In general, permafrost in Alaska has warmed between 0.3 and 6.0 • C since ground temperature measurements began between the 1950 and 1980s (Lachenbruch and Marshall, 1986;Romanovsky and Osterkamp, 1995;Osterkamp, 2007). Warming and thawing of near-surface permafrost may lead to widespread terrain instability in ice-rich permafrost in the Arctic (Jorgenson et al, 2006;Lantz and Kokelj, 2008;Gooseff et al, 2009;Jones et al, 2015;Liljedahl et al, 2016) and the subArctic Jorgenson and Osterkamp, 2005;Lara et al, 2016). Such land surface changes can impact vegetation, hydrology, aquatic ecosystems, and soil-carbon dynamics (Grosse et al, 2011;Jorgenson et al, 2013;Kokelj et al, 2015;O'Donnell et al, 2011;Schuur et al, 2008;Vonk et al, 2015).…”
mentioning
confidence: 99%
“…In general, permafrost in Alaska has warmed between 0.3 and 6.0 • C since ground temperature measurements began between the 1950 and 1980s (Lachenbruch and Marshall, 1986;Romanovsky and Osterkamp, 1995;Osterkamp, 2007). Warming and thawing of near-surface permafrost may lead to widespread terrain instability in ice-rich permafrost in the Arctic (Jorgenson et al, 2006;Lantz and Kokelj, 2008;Gooseff et al, 2009;Jones et al, 2015;Liljedahl et al, 2016) and the subArctic Jorgenson and Osterkamp, 2005;Lara et al, 2016). Such land surface changes can impact vegetation, hydrology, aquatic ecosystems, and soil-carbon dynamics (Grosse et al, 2011;Jorgenson et al, 2013;Kokelj et al, 2015;O'Donnell et al, 2011;Schuur et al, 2008;Vonk et al, 2015).…”
mentioning
confidence: 99%
“…From analysis of optical satellite images with sub-meter resolution, we found obvious development of polygonal networks after the fire, which is often found in areas of thermokarst (e.g., [28,29]). Although optical imagery cannot measure ground subsidence, it provides strong evidence of thermokarst development from changes in surface morphology.…”
Section: Thermokarst Evidence From Optical Imagery and Ground Truth Smentioning
confidence: 99%
“…Induced subsidence gradually stabilized as surface vegetation recovered, acting as a modulator of surface energy exchange, which had been enhanced by the combustion of surface vegetation and organic mat. Regarding the following years after 2010, when ALOS observation was not obtained, Jones et al [29] reported that LiDAR-derived subsidence between 2009 and 2014 was about 6 cm/year as a spatial average for burned Yedoma upland areas. They also reported that visual analysis of high-resolution satellite imagery indicated marked ice wedge degradation between 2011 and 2014, while there were subtle differences in image texture between 2008 and 2011.…”
Section: Spatial Resolution and Variation Of Captured Thermokarst Submentioning
confidence: 99%
“…Fires are known to occur in the tundra of northern Alaska but are uncommon [39]. The recent large fire near the Anaktuvuk River, visible on Figure A6, indicates that fire activity within the Tundra Biome could increase with climate warming, which could exacerbate thermokarst [40,41]. Severe fires accelerate thermokarst by removing the insulating soil organic layer, allowing summer heat to penetrate and thaw the permafrost [42].…”
Section: Change Typesmentioning
confidence: 99%